Caracas Declaration “On the bicentennial of the struggle for independence towards the path of our liberators” - Estados Latinoamericanos y Caribeños, Comunidad de (2012)
Agreement signed by the Heads and Heads of State and Government of the countries of Latin America and the Caribbean, meeting in Caracas, Bolivarian Republic of Venezuela, on December 2 and 3, 2011, within the framework of the III Summit of Latin America and the Caribbean on Integration and Development (CALC) and the XXII Summit of the Rio Group, and in the year of the commemoration of the Bicentennial of the Independence of Venezuela, and in memory and tribute to the transcendental historical work of El Liberator Simón Bolivar.